Valuations of skew quantum polynomials - Chaparro Acosta, Cristian Arturo (2015)
In this paper, we extend some results obtained by Artamonov and Sabitov for quantum polynomials to skew quantum polynomials and quasi-commutative bijective skew Poincaré?Birkhoff?Witt (PBW) extensions. Moreover, we find a counterexample to the conjecture proposed in [V. A. Artamonov, Quantum Polynomial, Advances in Algebra and Combinatorics (World Scientific, 2008)].